Hydrogen sulfide enhances salt tolerance in sorghum by activating the chloroplastic AsA–GSH cycle to sustain photosynthesis - Liu, Chang; Liu, Sitong; Hu, Xin; Shi, Xiaolong; Liu, Chunjuan; Sun, Lu; Zhou, Yufei (Frontiers in Plant Science, 2025)
Soil salinization poses a severe threat to global food security by reducing crop productivity, particularly in semi-arid regions where sorghum (Sorghum bicolor L.) is a major cereal crop. Hydrogen sulfide (H₂S) has recently been recognized as a signaling molecule involved in plant stress tolerance. However, its role in regulating the chloroplastic ascorbate–glutathione (AsA–GSH) cycle and photosynthetic performance in sorghum under salt stress remains unclear. To investigate the potential regulatory role of exogenous H₂S, sorghum seedlings were subjected to salt stress with or without sodium hydrosulfide (NaHS, an H₂S donor). Physiological, biochemical, and chlorophyll fluorescence parameters were assessed to evaluate growth performance, antioxidant capacity, and photosynthetic responses. The concentrations of reduced and oxidized forms of ascorbate (AsA/DHA) and glutathione (GSH/GSSG), together with the activities of key enzymes in the AsA–GSH cycle, were determined. Salt stress significantly inhibited sorghum seedling growth, enhanced reactive oxygen species (ROS) accumulation, and disrupted redox homeostasis. Exogenous H₂S alleviated these effects by stimulating the AsA–GSH cycle in chloroplasts. H₂S treatment maintained higher levels of reduced AsA and GSH while promoting moderate accumulation of DHA and GSSG, accompanied by elevated activities of ascorbate peroxidase (APX), glutathione reductase (GR), dehydroascorbate reductase (DHAR), and monodehydroascorbate reductase (MDHAR). Moreover, H₂S improved photosynthetic performance by maintaining chlorophyll content and chloroplast ultrastructure, optimizing chlorophyll fluorescence parameters, and protecting photosystem II (PSII) from photoinhibition. Enhanced electron transfer from the PSII reaction center to plastoquinone further indicated an improved capacity for energy dissipation under salt stress. These findings demonstrate that exogenous H₂S confers salt tolerance in sorghum by activating the chloroplastic AsA–GSH redox cycle and preserving photosynthetic efficiency. The study highlights H₂S as a critical mediator of chloroplast redox regulation, providing an effective strategy for enhancing sorghum resilience to soil salinization and promoting sustainable agricultural production.